Exploring the Potential of a Tailored Executive Functioning Training Program for Children with Congenital Heart Disease: A Brief Report. - Oppelaar, Eveline; Breur, Johannes Mpj; Wijnroks, Lex; Schappin, Renske (Developmental Neurorehabilitation, 2024)
The aim of this pilot study was to explore whether executive functioning (EF) problems of children with severe congenital heart disease (CHD) could be improved through a personalized EF-training program. Eleven preschool-aged children (mean age = 62 months, SD = 6) received a standardized test battery. Eight children were eligible for training and six children participated in the training and posttest. Due to the small sample size, only effect sizes were analyzed. Clinically relevant improvements were found with large effect sizes. Findings indicate that a personalized EF-training program could be effective in improving EF of children with severe CHD. Further research is needed.